ANALISIS PERATAAN LABA DAN FAKTOR.FAKTOR YANG MEMPENGARUHI: STUDI EMPIRIS PADA PERUSAHAAN DI INDONESIA - Deasy Kustiani; Erny Ekawati (Fakultas Bisnis UKDW, 2006)
Incotne smoothing practice is a common phenomenon and incurred in severql countries. Income smoothing is defined as the way used by the management to reduce the fluctuations of reported income to achieve the target income either artifrcially (through accounting m,ethod) or economically(through transaction)This research examines factors that can be identified with the frequenq) of income smoothing practice arnong listed /irms in Indonesian capttil Market Directory (ICMD). The factors being examined were size, net profrt margin, operating leverage and industrial sectors. To determine the frequency of incorne,smoothing practice, Eckel Index wai used. Theobject of income smoothing in this-researeh is net income. The total sample is 276 lirms, /ive years from 1999-2003. The result of Eckel index calculation showed that income smoothing is also practiced by listed /irms in ICMD. The test results of regression showed that size, net profit margin, operating leverage, industrial sectors are the variables having a significance influence on income smooting practice.Keyword: Income Smoothing,Earnings Management